STUDI KOMPARATIF MINAT SISWA SMKN RSBI DAN SMAN RSBI DI KABUPATEN PAMEKASAN TERHADAP PEMBELAJARAN DIKJASORKES - Nofa Risman Hidayat; - Asim; - Sulistyorini (Jurnal Pendidikan Jasmani, 2014)
Abstract: This study aims to identify and assess the student’s interests SMK RSBI and SMA RSBI and know the difference between a student's interests SMK RSBI and SMA RSBI in Pamekasan Dikjasorkes to learning. Using descriptive quantitative method and comparative survey design students’ interest towards learning among students Dikjasorkes RSBI with SMA SMK Negeri RSBI in Kabupeten Pamekasan. The results of this study showed that the average student interest by 114 SMK RSBI scores were in the range 93.6 to 115.1 including categories for medium and SMAN RSBI score of 108.6 in the range 93.6 to 115.1 including medium category. T-test results show the value of Sig. (0.009)